ANALISISPENGARUH PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN AIR MINUM PADA PT. SARIGUNA PRIMA TIRTA - AM, Sanusi; Jariah, Ainung (Jurnal Ekonomi Balance, 2016)
This study aims to determine the effect of consumer behavior analysis in drinking water purchasing decisions at PT. sariguna prima tirta. The data used in this study is the primary data obtained from the questionnaire. The sample of this research is data about PT. sariguna prima Tirta. The method of analysis is data obtained from the results of research by using descriptive analysis, the analysis technique used is multiple regression to test the results of data collection from each reponden. The results showed that the variables of motivation and welfare simultaneously have a significant effect on the purchase decision of drinking water at PT. sariguna prima tirta.